Comparison of Campylobacter contamination levels on chicken carcasses between modern and traditional types of slaughtering facilities in Malaysia - Rejab S.B.M. (2014)
A total of 360 samples including fresh fecal droppings, neck skins, and swab samples was collected from 24 broiler flocks and processed by 12 modern processing plants in 6 states in Malaysia. Ninety samples from 10 traditional wet markets located in the same states as modern processing plants were also collected. Microbiological isolation for Campylobacter was performed following ISO 10272-1:2006 (E). The overall rate of contamination for Campylobacter in modern processing plants and in traditional wet markets was 61.1% (220/360) and 85.6% (77/90), respectively. Campylobacter jejuni was detected as the majority with approximately 70% for both facilities. In the modern processing plants, the contamination rate for Campylobacter gradually declined from 80.6% before the inside-outside washing to 62.5% after inside-outside washing and to 38.9% after the post chilling step. The contamination rate for Campylo-bacter from processed chicken neck skin in traditional wet markets (93.3%) was significantly (P<0.01) higher than in modern processing plants (38.9%). © 2012 The Japanese Society of Veterinary Science.